Peningkatan Keterampilan Menulis Cerpen Menggunakan Model Auditory, Intellectually, Repetition (Air) Pada Siswa Kelas IV SD Inpres Bontosunggu Kabupaten Gowa - Bahri, Aliem; Nadira , Nurwindah; Asnidar , Anin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study was to improve short story writing skills using the Auditory, Intellectually, Repetition (AIR) model in Class IV SDI Bontosunggu. The type of this research is classroom action research. The results showed that learning to write short stories cycle I was unsatisfactory and the class atmosphere was less conducive. Teachers have not carried out learning activities to the fullest, so there are still students who find it difficult to express ideas or ideas in writing short stories. The learning process in cycle II was more effective and satisfying after improvements were made to the problems in cycle I. In cycle II students were more enthusiastic and motivated to take part in learning, worked together in groups, and it was not difficult when expressing ideas in writing short stories. This increase can be seen from the average student score as a whole in cycle I of 69.5 while the score in cycle II was 86.1 with a percentage increase of 16.6%. All aspects of assessment are classified as very poor in cycle I and increase to a good category in cycle II.